METTL3 regulates ASMCs proliferation and M2 macrophage polarization via mediating the m6A methylation of TIMMDC1 in asthma - Shihao Zhang; Xiurong Wen; Lin Liu (Immunobiology)
Background: Asthma has widespread prevalence and can affect the lives of children, adolescents, and adults. While methyltransferase-like 3 (METTL3) and translocase of inner mitochondrial membrane domain-containing protein 1 (TIMMDC1) have been associated with various diseases, however, the role of METTL3 and TIMMDC1 in asthma mechanisms is still unclear. Methods: The mRNA and protein expression were examined using qRT-PCR and western blot. EdU and transwell assay were employed to examine the cell proliferation and invasion. The ability of apoptosis was analyzed using flow cytometry and qRT-PCR. The activation of M2 macrophages was evaluated via flow cytometry and qRT-PCR. IL-13 level was tested via ELISA assay. The methylation site of METTL3 was predicted using SRAMP sites. Me-RIP assay was used to analyze the methylation of METTL3. The binding site between methyltransferase METTL3 and TIMMDC1 was predicted by RBP suit, and the interaction between METTL3 and TIMMDC1 was confirmed through RIP. Results: The TIMMDC1 levels were increased in asthma, and TIMMDC1 promoted PDGF-BB-induced human airway smooth muscle cells (ASMCs) proliferation, migration, and M2 macrophage polarization. Furthermore, METTL3 inhibited TIMMDC1 expression via mediating m6A methylation. Besides, up-regulated METTL3 suppressed PDGF-BB-stimulated ASMCs proliferation, migration, and M2 macrophage polarization. Ultimately, METTL3 repressed PDGF-BB-induced ASMCs procession by inhibiting the TIMMDC1 expression. Conclusions: The m6A methyltransferase METTL3 suppressed the procession of PDGF-BB-induced ASMCs by inhibiting the TIMMDC1 expression. Collectively, this study might provide novel insights for the treatment of asthma.